Pengaruh Penambahan Surfaktan Estolida dan Digliserida pada Pelumas Minyak Goreng terhadap Temperatur Mesin dan Daya - Alfianto Alfianto; Haris Puspito Buwono (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Lubricating oil is a type of fluid needed by a machine to carry out work steps. Significant changes in the temperature of the lubricating oil viscosity until it is too low makes the engine components less lubricated, which causes the engine components to heat up quickly because the friction between the metals that occurs becomes greater. Lubricant that is of poor quality can cause deposits to appear in the engine room which results in the engine working harder. The aim can be achieved in this research by varying the lubricating oil with a mixture of Estolide and Diglyceride surfactant percentages of (2.5%, 5% and 7.5%). This test was carried out on a petrol motorbike with a combustion chamber volume of 125cc with standard conditions. The data that will be taken in this research includes engine temperature and power. The power testing method using a dynamometer and lubricant with cooking oil mixed with 7.5% estolide surfactant after heating produces an average value of 6.52 HP which has a higher average value than oil with a value of 5.37 HP